2008
DOI: 10.3174/ajnr.a0917
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Clopidogrel-Related Platelet Inhibition: Correlation of Nonresponse with Clinical Outcome in Supra-Aortic Stenting

Abstract: BACKGROUND AND PURPOSE:Clopidogrel and aspirin are antiplatelet medications used in patients intended for endovascular stent placement. Although various studies have investigated individual responsiveness to clopidogrel in patients undergoing coronary interventions, there are no studies regarding patients undergoing stent placement of supra-aortic arteries supplying the brain. We analyzed platelet function in a near-patient setting to determine the effects of antiplatelet treatment in neurologic patients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
67
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 47 publications
3
67
0
1
Order By: Relevance
“…21 Our present results showed that ADP inhibition was the independently predictive factor of ischemic lesions following stent insertion, which means that P2Y12 inhibitor resistance was associated with a higher risk of thromboembolic complications after stent placement. 9,24 Similar results have also been reported in patients undergoing coronary stent placement or in patients with intracranial and extracranial stenosis following stent insertion. 7,14,24 Therefore, the ADP inhibition may be a critical factor for predicting thromboembolic complications following stent treatment, and sufficient inhibition of the platelet reactivity may reduce the occurrence of thromboembolic complications.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…21 Our present results showed that ADP inhibition was the independently predictive factor of ischemic lesions following stent insertion, which means that P2Y12 inhibitor resistance was associated with a higher risk of thromboembolic complications after stent placement. 9,24 Similar results have also been reported in patients undergoing coronary stent placement or in patients with intracranial and extracranial stenosis following stent insertion. 7,14,24 Therefore, the ADP inhibition may be a critical factor for predicting thromboembolic complications following stent treatment, and sufficient inhibition of the platelet reactivity may reduce the occurrence of thromboembolic complications.…”
Section: Discussionsupporting
confidence: 75%
“…9,24 Similar results have also been reported in patients undergoing coronary stent placement or in patients with intracranial and extracranial stenosis following stent insertion. 7,14,24 Therefore, the ADP inhibition may be a critical factor for predicting thromboembolic complications following stent treatment, and sufficient inhibition of the platelet reactivity may reduce the occurrence of thromboembolic complications. However, sufficient inhibition of platelet reactivity may increase the risk of bleeding complications, especially for intracranial hemorrhage.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[18][19][20][21] Two previously published studies in the cardiac population that specifically address bleeding complications in the context of antiplatelet medication showed a strong correlation between clopidogrel hyper-response and bleeding risk. Sibbing et al 11 found that 38% of patients undergoing percutaneous coronary intervention were hyper-responders, who had a higher incidence of major bleeding (2.2%) compared with the remainder of the population (0.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy with aspirin and a thienopyridine (commonly clopidogrel) is used to prevent endovascular thrombotic complications, especially in cerebrovascular stent placement. 10 However, up to 66% of patients undergoing stent placement show resistance to clopidogrel ("nonresponders"), and a lesser proportion are resistant to aspirin. [11][12][13][14] Antiplatelet resistance has been associated with thromboembolic complications, 10,11 though the inhibition threshold and timing of platelet testing is controversial, 15,16 as is the pharmacologic management of nonresponders.…”
mentioning
confidence: 99%